Public Opinion and Sensus Fidelium - Agemir Bavaresco (Daimon)
Public opinion and religious opinion are located within plural societies, connected to social networks. The experience of the phenomenon of public opinion by the believers interacts with the experience of religious opinions. What are the mediations employed by the sensus fidelium to explain the contradictions between public and religious opinion? This article discusses the proximity between public and religious opinions through the categories of publicity, contradiction, utility and truth. In networked societies, the faithful exercise the right to express their opinions and religious convictions. The phenomenon of the sensus fidelium immediately evidences the experience of faith of the believers as subjective convictions and religious opinions. Afterwards, these opinions are mediated by the collegiate spheres of the Church, expressing the coherence of the belief, that is, its truth. The proximity between public and religious opinions points to more complex scenarios for the Church and the believers.